Eco-urban residential towers : a green community on a high rise neighborhood - Usero, Jennelyn M. (Manila : National University, 2010)
This study will cater to the needs of users, building and environment so as to generate perfect harmony for green community. This will also encourage responsiveness and awareness that will help increases the quality of life in the city.
Title page -- Project title page -- Approval sheet -- Dedication -- Acknowledgement -- Chapter 1. problem justification -- Chapter 2. Research methodology -- Chapter 3. terms of references -- Chapter 4. Gathering, collation and analyses of data -- Chapter 5. project details and final design solution -- Chapter 6. Findings, conclusion and recommendations -- Bibliography -- Curriculum vitae.
Includes bibliographical references.